Pandemi Covid-19 dan Praktik Keagamaan - Siregar, Parluhutan; Hsb, Mara Ongku (STAIN Bengkalis, 2023)
Religious activities during the Covid-19 pandemic seem to have to come to terms with the current situation where religious messages are conveyed very quickly and easily, so that anyone who wants to find out religious propositions will not find it difficult to find them because everything is instantaneous. The research method used in this study used a library research method with a qualitative approach to obtain descriptive data. The collection of data taken in this study by conducting library research, the source of research data comes from sources that have been collected from the library. Research results During the Covid-19 pandemic, religious activities such as religious learning, religious practices were applied through platforms such as zoom applications, google meet, which usually face-to-face but do not reduce the interest of the public or educated people to participate in religious activities, religious learning is instantaneous by society and scholars today. Religion has responded to the covid-19 pandemic as a form. The MUI fatwa has issued a fatwa on religious guidelines on worship and others vertically as a guide for the Muslim community.